2011
DOI: 10.1136/amiajnl-2011-000154
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid methods for improving information access in clinical documents: concept, assertion, and relation identification

Abstract: On the one hand, the authors confirm that the use of only machine-learning methods is highly dependent on the annotated training data, and thus obtained better results for well-represented classes. On the other hand, the use of only a rule-based method was not sufficient to deal with new types of data. Finally, the use of hybrid approaches combining machine-learning and rule-based approaches yielded higher scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Most criteria were words or UMLS CUIs that describe facial fractures or orbital anatomy. Support Vector Machines (SVM) have been previously shown to be very successful in text classification, including the medical domain, but provide no way of verifying the sensibility of the algorithm. Although we planned to perform only decision trees as a transparent form of machine learning, we did confirm that the results of classification using SVM (using the WEKA SMO classifier) showed similar performance…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most criteria were words or UMLS CUIs that describe facial fractures or orbital anatomy. Support Vector Machines (SVM) have been previously shown to be very successful in text classification, including the medical domain, but provide no way of verifying the sensibility of the algorithm. Although we planned to perform only decision trees as a transparent form of machine learning, we did confirm that the results of classification using SVM (using the WEKA SMO classifier) showed similar performance…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, more generalizable automated outcome classification pairing NLP software and machine learning techniques are now possible. This approach has shown to have the potential to code EHR data, although most prior studies have been performed on documents mocked up for NLP testing and never validated on real‐world data.…”
mentioning
confidence: 99%
“…After preliminary experiment we found that we did not have For extracting relations among entities we considered all sentences having more than one entities in each discharge summary to check whether any relation exists between them or not. In our experiment we assume that entities and their types are already known like other existing works (Rink et al, 2011;Minard et al, 2011a;Minard et al, 2011b). We created data sample for every pair of entities present in the sentence and labeled it with the existing relation type.…”
Section: Dataset and Experimental Settingsmentioning
confidence: 99%
“…39 Classification is the most common method in textual analysis; this can be done using Perceptron, Support Vector Machine (SVM), Naive Bayes (NB), k-NN, Maximum Entropy Model (MEM), and Decision Tree (DT). 42 Optimal features need to be defined for the selected classifier, including sentencelevel, entity-level, and token-level features, as shown in Table 1.…”
Section: Semantic Recognition Layermentioning
confidence: 99%